Brand Engagement and Word of Mouth - I Nyoman Nurcaya; Ni Made Purnami (Udayana Journal of Social Sciences and Humanities, 2017)
Modern marketing using social media such as Facebook allow the marketers to have a two-way interaction with the consumers, let them give appreciation each other, allow the consumers to leave comments about the products, and the company can directly provide answers to the consumers’ questions and complaints. The purpose of this study is to examine the effect of brand engagement on word of mouth. This research was conducted in Denpasar. The respondents are those who have clicked “like”, “share”, or “comment” button upon a particular brand on Facebook. The data were collected by distributing questionnaires to the respondents who have met the criteria. This study used Partial Least Square (PLS) analysis technique. The results show that 1) Inner self has positive and significant impact on brand love Oriflame; 2) Social self has positive and significant impact on brand love Oriflame; 3) Brand love has positive and significant impacton Word of Mouth Oriflame on Facebook.